Lembranças de minha vida: da infância à formação - SOUZA, Josias Machado de (2024)
This present work aims to address several aspects of my life trajectory, highlighting many moments of my personal childhood, as well as the challenges of my school trajectory in which it made me recover from my memory many memories, especially those that marked my trajectory of life, as well as the difficulties found in the professional trajectory to work as a teacher in the initial series of basic education. Bringing also a little about the importance of playfulness in the educational field mainly in the teaching of basic education, emphasizing my academic trajectory in which are present several challenges in which I lived during this process of my formation in the university making me reflect on my teaching practice. The stories narrated here are life experiences that provided my building in the process of this long journey of my academic formation.